Number 48 (July 2005) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2005)
(July 2005) - An analysis of the Menidia complex in the Mississippi River Valley and in two nearby minor drainages. By Royal D. Suttkus, Bruce A. Thompson, and Jason K. Blackburn Minutes, Business Meeting, 30th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: fishes; menidia; complex; mississippi river; drainage